AVALIAÇÃO DO CRESCIMENTO E DA PRODUÇÃO DE ÓLEO ESSENCIAL DAS FOLHAS DE Ocimum gratissimum L. (LAMIACEAE) SOB INFLUÊNCIA DE TAXAS DE APLICAÇÃO DE ÁGUA E DE NITROGÊNIO. - VILANOVA, Crisálida Machado (2018)
Ocimum gratissimum L. (clove basil) is a popular medicinal plant with vast potential for use in the pharmaceutical, cosmetic and food industries. Water and nitrogen can not only affect the overall development of the vegetable, but alter its chemical composition and, consequently, the quality of products made from that vegetable raw material. The effects of different water application rates, 60% (I60), 70% (I70), 80% (I80), 90% (I90), 100% (I100) and 110% (I110) of field capacity (FC), and nitrogen fertilisation, 0 (N0), 40 (N2), 80 (N4) and 160 (N8) kg of nitrogen/ha, on growth and essential oil of this species were studied. The experiment was carried out in 2006 for 60 days in a greenhouse in a completely randomised design with three replicates. The isolated volatile constituents were analysed by GC–MS. The water deficiency was determinant for the appearance of wilting and staining on the leaves of cimum. gratissimum, while the symptoms of necrosis, apical necrosis, abscision and chlorosis presented correlation only with nitrogen deficiency. There was a significant (p < 0.05) effect on the growth and production of Ocimum gratissimum essential oil for water application rate, nitrogen and the interaction between these two factors. The maximum values of width (8.3 cm), length (11.5 cm) and number of leaves (301.3), leaf dry matter (52.5 g/plant), essential oil content (1.58%) and oil yield (82.9 mL/plant) were obtained in the I110N8 treatment. Twenty compounds were identified in each clove basil essential oils with predominance of phenylpropanoids in the I110N8 treatment, and of monoterpenes in the other treatments. The water application rate above field capacity together with nitrogen dose higher than normally recommended improves plant growth and increases the production of its essential oil by modifying the metabolic pathway.